2011
DOI: 10.1021/om201026n
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Reversible 1,3-Dipolar Cycloaddition of Aryl Ketonitrones to Platinum(II)-Bound Nitriles: Synthetic, Structural, and Theoretical Studies

Abstract: The reaction between trans-[PtCl2(NCR)2] (R = Et 1, NMe2 2, NEt2 3, NC5H10 4) and the acyclic triaryl ketonitrones Ph2CN­(O)­C6H4R′-p (R′ = H 5, Me 6, Cl 7, OMe 8) proceeds as a facile and consecutive two-step intermolecular cycloaddition to give the mono-cycloaddition products trans-[PtCl2(NCR)­{N a C­(R)­ON­(C6H4R′-p)­C b Ph2}](a−b) (R/R′ = Et/H 9, Et/Me 10, Et/Cl 11, Et/OMe 12, NMe2/H 13, NMe2/Me 14, NMe2/Cl 15, NMe2/OMe 16, NEt2/H 17, NEt2/Me 18, NEt2/Cl 19, NEt2/OMe 20, NC5H10/H 21, NC5H10/Me 22, NC5H10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…[18][19][20]28 These distinctions were recognized at qualitative level when the same metal-mediated reactions of NCR′ and NCNR 2 ligands furnish different products, [18][19][20]29 or at quantitative level when kinetic experiments showed that NCNR 2 species exhibit an unexpectedly high activation toward metalmediated 1,3-dipolar cycloaddition of nitrones as compared to NCAlk. 30,31 In addition, synthetic experiments indicate that dialkylcyanamide ligands, despite a strong donor character of the NR 2 group (that becomes evident upon inspection of the Pickett and Lever parameters for NCNR 2 32 ), exhibit high reactivity toward nucleophilic addition. 33 However, all these differences were observed exclusively at a qualitative level and no convincing quantitative or semi-quantitative data were reported.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20]28 These distinctions were recognized at qualitative level when the same metal-mediated reactions of NCR′ and NCNR 2 ligands furnish different products, [18][19][20]29 or at quantitative level when kinetic experiments showed that NCNR 2 species exhibit an unexpectedly high activation toward metalmediated 1,3-dipolar cycloaddition of nitrones as compared to NCAlk. 30,31 In addition, synthetic experiments indicate that dialkylcyanamide ligands, despite a strong donor character of the NR 2 group (that becomes evident upon inspection of the Pickett and Lever parameters for NCNR 2 32 ), exhibit high reactivity toward nucleophilic addition. 33 However, all these differences were observed exclusively at a qualitative level and no convincing quantitative or semi-quantitative data were reported.…”
Section: Introductionmentioning
confidence: 99%
“…pyrroline N-oxide) have been studied. [582,583] The reaction of nitrile complexes with imidazoline N-oxides created "a novel type of heterocycles 137, which do not exist without a metal center". [584] www.zaac.wiley-vch.…”
Section: Nitrile Complexesmentioning
confidence: 99%
“…In the past decade, a great attention has been paid to electrophilic activation of the C≡N bond in nitriles (Bokach, 2010;Bokach et al, 2011a;Bokach et al, 2011b;Kritchenkov et al, 2011;Kritchenkov et al, 2012;Kukushkin & Pombeiro, 2002;Makarycheva-Mikhailova et al, 2007). In a addition an interest in compounds which contain borane clusters is caused by their potential application in medicine, homogeneous catalysis, for non-linear optics and luminescent materials creation, as potential metal extractants, agents for anion recognition and building blocks for coordination polymers creation, etc (Dash et al, 2011).…”
Section: S1 Commentmentioning
confidence: 99%